Employee Well-being dan Stres Kerja terhadap Pengembangan Karier di Era Kompetisi Profesional - Zulkarnaini; Irfan Arif Husen; Rutinaias Haholongan (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
The purpose of this study was to examine how work stress and employee well-being impact career advancement. This study used a quantitative approach, and data were collected through questionnaires from one hundred active employees. Data analysis was performed using multiple linear regression and SPSS. The results showed that work stress had a negative and significant effect on career development, while employee wellbeing had a positive and significant effect. The coefficient of determination (R2) of 0.465 indicates that work stress and employee well-being explain 46.5% of the variance in the career development variable. Other variables outside the study influence the remaining variables. High levels of work stress can hinder career development, but employee well-being plays a crucial role in enhancing career development. Therefore, organizations need to improve employee well-being and effectively manage work stress to support optimal career development and employee performance.